Management of eosinophil-associated inflammatory diseases: the importance of a multidisciplinary approach - Quirce, Santiago; Cosío, Borja G.; España, Agustín; Blanco, Ricardo; Mullol, Joaquim; Santander, Cecilio; del Pozo, Victoria (Frontiers in Immunology, 2023)
Elevated eosinophil counts in blood and tissue are a feature of many pathological processes. Eosinophils can migrate and accumulate in a wide variety of tissues and, by infiltrating a target organ, can mediate the development of several inflammatory diseases. The normalization of eosinophilia is a common biomarker of a treatable trait and can also be used as a prognostic and predictive biomarker since it implies a reduction in type 2 inflammation that contributes to disease pathogenesis. Biological therapies targeting this cell type and its proinflammatory mediators have been shown to be effective in the management of a number of eosinophilic diseases, and for this reason they constitute a potential common strategy in the treatment of patients with various multimorbidities that present with type 2 inflammation. Various biological options are available that could be used to simultaneously treat multiple target organs with a single drug, bearing in mind the need to offer personalized treatments under the umbrella of precision medicine in all patients with eosinophil-associated diseases (EADs). In addition to reviewing these issues, we also discuss a series of perspectives addressing the management of EAD patients from a multidisciplinary approach, with the collaboration of health professionals from different specialties who manage the different multimorbidities that frequently occur in these patients. We examine the basic principles of care that this multidisciplinary approach must cover and present a multidisciplinary expert opinion regarding the ideal management of patients with EADs, from diagnosis to therapeutic approach and follow-up.